INSTITUTE OF PRE-EMPTION AND MEDIATION IN ENSURING THE RIGHTS OF INDIVIDUAL ENTREPRENEURSHIP SUBJECTS: PRACTICE AND PROSPECTS - Rozhkova, Anna (Administrative and Criminal Justice, 2019)
This paper is devoted to the issues of using prevention institutes and the mediation in rights ensuring institute of individual enterprise in the sphere of the control by public authorities. The aim of the research is to analyze the peculiarities of practice to use the methods of inspection by the state supervision agency in order to ensure the rights of    individual enterprise’s subject. The aim of the research is linked to the contradictory problems during the implementation of inspection’s legal nihilism of government officials’ right treatment during of inspections and possible essential risks for IE and effect lowering of rights securing. The novelty of the work is expressed in topicality and justification of the prevention institute in order to minimize the risks to ensure the legal consciousness and the rights of individual enterprise. According to this aim several tasks have been solved and as result some basic principles have been formulated and the conclusions were drawn. More precise definitions were provided to the understanding of distinction “government control” and “checking” via the assistance of intercommunication establishment through the general and special principles of material and procedural mutual concern, which are topical for an individual enterprise owing to minimization of administrative risks. Having been based the efficacy of Institute of prevention as the method of preventive measure and influence on the behavior of the characters of individual enterprise. So in sphere of rights ensuring of characters of Individual enterprise the principles of conclusive reasons for conducting preliminary verifications was suggested. The efficiency of the mediation institute in the sphere of public rights was justified.